2010
DOI: 10.3109/14767058.2010.511330
|View full text |Cite
|
Sign up to set email alerts
|

Unusual high rate of asymptomatic maternal parvovirus B19 infection associated with severe fetal outcome

Abstract: Asymptomatic parvo B19 infection is associated with poor fetal outcome much more than we presumed previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In case of a maternal infection, transmission to the fetus occurs in one third to one half of cases, with a risk of adverse fetal outcome of about 10% [13,[18][19][20][21]22 & ,23]. Brkic et al [24] recently analyzed 176 pregnancies for asymptomatic B19V infection, and found a significantly higher prevalence of B19V in second trimester women with symptoms of miscarriage as compared to uncomplicated controls. The risk of fetal complications is believed to be greatest when infection occurs in the first 22 weeks of pregnancy [25].…”
Section: Epidemiologymentioning
confidence: 98%
“…In case of a maternal infection, transmission to the fetus occurs in one third to one half of cases, with a risk of adverse fetal outcome of about 10% [13,[18][19][20][21]22 & ,23]. Brkic et al [24] recently analyzed 176 pregnancies for asymptomatic B19V infection, and found a significantly higher prevalence of B19V in second trimester women with symptoms of miscarriage as compared to uncomplicated controls. The risk of fetal complications is believed to be greatest when infection occurs in the first 22 weeks of pregnancy [25].…”
Section: Epidemiologymentioning
confidence: 98%
“…B19V usually causes a mild, self‐limiting, and exanthematous disease in childhood; it can cause cytopenia in immunocompromised hosts and intrauterine fetal death in pregnant women with primary infection [1]. Infection usually takes place through respiratory droplets but the virus can also be transmitted by blood and vertically from mother to fetus [2].…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…33 Brkic found asymptomatic acute parvovirus B19 infection rate as 22.72% among pregnant women with spontaneous abortion. 26 On the other hand, Enders et al reported fetal hydrops risk as 4.2% after gestational parvovirus B19 infection. 34 Gratacos et al reported the incidence of acute infection during pregnancy as 3.7% and the incidence of fetal loss caused by parvovirus as 1.66%.…”
Section: Clinical Manifestations and Transmission Of Parvovirus B19 Imentioning
confidence: 99%
“…In the third semester, fetal death is reported in approximately 7% of infected pregnant women. 25,26 Fetal and maternal infection can also be asymptomatic. 25,27 When a pregnant woman has acute parvovirus B19 infection, the transmission rate to fetus is about 33%, and the risk for fetal death is 9%.…”
Section: Clinical Manifestations and Transmission Of Parvovirus B19 Imentioning
confidence: 99%
See 1 more Smart Citation